BREF HISTORIQUE D’UN SYMBOLE DE LA GEOGRAPHIE URBAINE : LA PLACE TAKSIM, ISTANBUL - Valentina-Mariana Manoiu; Razvan-Madalin Spiridon (European Scientific Journal, ESJ, 2014)
A brief history of an urban geographic symbol: Taksim Square, Istanbul. A city’s urban squares represent a transposition of a spiritual public sphere in the material world. The tangible and material openness of these urban areas allows a spontaneous openness of the heart and soul. The urban public squares can bring people together in a peaceful and friendly manner, allowing city dwellers to move freely at any given moment, all year around. The purpose of this paper is to present the history of a beautiful and famous square, named Taksim, located in the equally famous transcontinental city of Istanbul. Taksim Square is the largest urban open space available in the famed metropolis. The historical analysis begins with the birth of Taksim Square, in the eighteenth century, taking it all the way to its complex present. Throughout our brief historical analysis, we avoided any political reference or connection which might have emotionally derailed or distorted our objective study. We pointed out the main evolutionary stages of an urban geographic symbol, whose eco-architectural future will surely be just as tortuous as its’ past.